2020
DOI: 10.1155/2020/6761328
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Abattoir Waste for Bioenergy as Sustainable Management, Eastern Ethiopia, 2019

Abstract: Our environment is facing serious problems of high volumes of waste generation and inadequate disposal system in worldwide particularly in developing countries. There is also lack of studies on quantification of abattoir waste and lack of workers awareness towards abattoir waste. Therefore, the purpose of the study was to estimate abattoir waste for bioenergy potential as sustainable management. A cross-sectional study was conducted in four selected abattoirs of Eastern Ethiopia from January 1st, 2018 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Taking TS = 15%, = 1052 kg/m 3 was obtained and applied. Estimation of Possible Reduction of Green House Gas (GHG) Emissions: The decrease in GHGs by the production of biogas from abattoir waste was calculated using the mathematical computational method developed by IPCC and applied by Tolera and Alemu [21], expressed as GHG reduction potential of AD equal to the estimate of GHG emissions from dumping sites minus the estimate of GHG emissions from AD:…”
Section: Study Location Data Collection Methods and Quantificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking TS = 15%, = 1052 kg/m 3 was obtained and applied. Estimation of Possible Reduction of Green House Gas (GHG) Emissions: The decrease in GHGs by the production of biogas from abattoir waste was calculated using the mathematical computational method developed by IPCC and applied by Tolera and Alemu [21], expressed as GHG reduction potential of AD equal to the estimate of GHG emissions from dumping sites minus the estimate of GHG emissions from AD:…”
Section: Study Location Data Collection Methods and Quantificationsmentioning
confidence: 99%
“…Estimation of Possible Reduction of GHG Emissions: A model for computation proposed by the IPCC with default values for the various coefficients and used by Tolera and Alemu [21] was applied to estimate the values of GHG reduction potential in terms of t CO 2 eq, Figure 5. The aggregate GHG reduction potential by installation of AD plants at the 4 sites is 30.71 t CO 2 eq.…”
Section: Estimate Of Waste Generated Biomethane Electricity Biofertilizer and Methane Emission Mitigation Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large amount of wastes generated from the selected abattoirs in Eastern Ethiopia is simply discharged or released into the environment without any management system or treatment pond. 15 To reduce these problems, adequate knowledge and practice of proper waste management are of tremendous significance which considering the aforementioned hazards related to abattoir wastes coupled with other life limiting factors. 16…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the amount of solid waste generation depends on the scale of the slaughtering process. Improper disposal of abattoir waste not only affects the air and water quality but also increases the threats to human health due to the presence of pathogenic microbes [9]. It is reported that about one-third to one-half of the total weight of slaughtered animal remains as unutilized or partly utilized byproducts of livestock and poultry industry [10,11].…”
mentioning
confidence: 99%